Assessment of the feed additive consisting of endo‐1,3(4)‐beta‐glucanase and endo‐1,4‐beta‐xylanase (ROVABIO® ADVANCE) for chickens for fattening and reared for laying, laying hens, turkeys for fattening and reared for breeding, and minor poultry species for fattening and reared for laying for the renewal of its authorisation and for its extension of use to all poultry species (Adisseo France SAS) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the feed additive consisting of endo‐1,3(4)‐beta‐glucanase and endo‐1,4‐beta‐xylanase (produced with Talaromyces versatilis DSM 26702 and T. versatilis IMI 378536) (ROVABIO® ADVANCE) as a zootechnical additive (functional group of digestibility enhancers) in feed for all poultry species. The additive is currently authorised for chickens for fattening and reared for laying, laying hens, turkeys for fattening and reared for breeding, and minor poultry species for fattening and reared for laying. This scientific opinion concerns the request for the renewal of the authorisation of the additive for these species and the extension of use to all poultry species. The applicant provided evidence that the additive complies with the conditions of the authorisation. The FEEDAP Panel concluded that the additive remains safe for the target species, consumers and the environment, and that the extension of use to the new species would not affect these conclusions. Regarding user safety, the FEEDAP Panel reiterates its previous conclusion that the additive is not irritant to the skin or eyes and is to be considered a potential skin and respiratory sensitiser. There is no need for assessing the efficacy of the additive for chickens for fattening and reared for laying, laying hens, turkeys for fattening and reared for breeding, and minor poultry species for fattening and reared for laying in the context of the renewal of the authorisation. The FEEDAP Panel considers that the additive has the potential to be efficacious in all poultry species at a minimum inclusion level of 1100 VU endo‐1,4‐beta‐xylanase and 760 VU endo‐1,3(4)‐beta‐glucanase/kg complete feed.